Skin Toxicity as Predictor of Survival in Refractory Patients with RAS Wild-Type Metastatic Colorectal Cancer Treated with Cetuximab and Avelumab (CAVE) as Rechallenge Strategy - Davide Ciardiello (MDPI AG, 2021)
The single-arm phase II CAVE mCRC trial evaluated the combination of cetuximab plus avelumab as rechallenge strategy in RAS wild-type (WT) metastatic colorectal cancer (mCRC) patients, with clinical response to first-line anti-EGFR-based chemotherapy, who progressed and received a subsequent line of therapy. The correlation of skin toxicity (ST) and different clinico-molecular variables with overall survival (OS), progression-free survival (PFS) and response rate (RR) was assessed at univariate and multivariate analysis. A total of 33/77 (42.9%) patients experienced grade 2–3 ST and displayed median OS (mOS) of 17.8 months (CI 95%, 14.9–20.6); whereas 44/77 (57.1%) patients with grade 0–1 ST exhibited mOS of 8.2 months (CI 95%, 5.5–10.9), (hazard ratio (HR), 0.51; CI 95%, 0.29–0.89; p = 0.019). Median PFS (mPFS) was 4.6 months (CI 95%, 3.4–5.7) in patients with grade 2–3 ST, compared to patients with grade 0–1 ST with mPFS of 3.4 months (CI 95%, 2.7–4.1; HR, 0.49; CI 95%, 0.3–0.8; p = 0.004). Grade 2–3 ST (HR, 0.51; CI 95%, 0.29–0.89; p = 0.019) and RAS/BRAF/EGFR WT circulating tumor DNA (ctDNA) (HR, 0.50; CI 95%, 0.27–0.9; p = 0.019) had a statistically significant effect on OS at univariate analysis. At the multivariate analysis, RAS/BRAF/EGFR WT ctDNA status maintained statistical significance (HR, 0.49; CI 95%, 0.27–0.9; p = 0.023), whereas there was a trend towards ST grade 2–3 (HR, 0.54; CI 95%, 0.29–1.01; p = 0.054). Skin toxicity is a promising biomarker to identify patients with mCRC that could benefit of anti-EGFR rechallenge.